New tetrodotoxin analogs in Brazilian pufferfishes tissues and microbiome. (March 2020) - Tonon, Luciane A.Chimetto; de Azevedo, Gustavo P.R.; Monteiro, Afif F.; Bernardi, Darlon I.; Gubiani, Juliana R.; Ióca, Laura P.; Mattsson, Hannah K.; Moreira, Ana Paula B.; Gomes, Alexandre F.; Pires Junior, Osmindo R.; da S G Pedrosa, Carolina; Souza, Leticia R.Q.; et al.
Abstract: While tetrodotoxin (TTX) is commonly found in pufferfish tissues, it is unclear if bacterial symbionts isolated from pufferfish tissues can produce TTX. In this investigation, UPLC qTOF-MS/MS analysis of tissue extracts obtained from Sphoeroides spengleri and Canthigaster figuereidoi identified TTX in their composition, indicating their consumption is unsafe. UPLC qTOF-MS/MS analysis coupled with Molecular Networking indicated new TTX analogs (methyl-TTX, TTX-acetate, hydroxypropyl-TTX and glycerol-TTX). Bacterial extracts from sixteen strains revealed a compound with a [M+H] + ion at m/z 320.1088, identical to TTX. However, TTX itself was not detected in these cultures by UPLC-MS/MS. Neurotoxicity of Vibrio A665 purified fraction 2 (with precursor [M+H] + ion at m/z 320.1088) was significant in human neural stem cells (hNSCs), but the Nav blockage activity was not confirmed by the veratridine/ouabain essays, indicating a possible difference in the mechanism of action between the bacterium A665 purified fraction 2 and TTX. Vibrios symbionts of pufferfish point out involving in the production of TTX precursors. Graphical abstract: Image 1 Highlights: TTX was detected in all organs from Brazilian pufferfish C. figueiredoi and S. spengleri and their consumption is unsafe. First report on the TTX and analogs in pufferfish C. figueiredoi . Molecular Networking indicated new TTX analogs. TTX and analogs contents in pufferfish were determined by using the UPLC qTOF-MS/MS. Vibrios symbionts of pufferfish point out involving in the production of TTX precursors.